A Model Development of Literacy leadership for school administrators - Supising, Jiraporn; Boonrawd, Somkiet; Taweeboonyawat, Suriya; Chaichana, Ponlawat; Puthaprasert, Choocheep; Kosanpipat, Sirimas (มนุษยสังคมสาร (มสส.) คณะมนุษยศาสตร์และสังคมศาสตร์ มหาวิทยาลัยราชภัฏบุรีรัมย์, 2024)
The objectives of the research were 1) to synthesize the elements of literacy leadership for school administrators, 2) to study the problem situations and recommend feasible guidelines for developing literacy leadership for school administrators, 3) to develop a model of literacy leadership for school administrators, and 4) to propose policy proposals and practical proposals for promoting literacy leadership for school administrators. Instruments used in this research were a synthesis table, a checklist table, a semi-structured interview form, a drafted model, an examination form, and a meeting record form. Data were analyzed by frequency, percentage, and content analysis, classified by issues, and categorized into core elements. The results revealed as follows: 1. The synthesis results of the literacy leadership for school administrators consisted of seven elements and twenty-one sub-elements, 2. The problem situations and feasible guidelines consisted of nine issues, 3) The development of a model of literacy leadership for school administrators comprised five model components as follows: principles, objectives, operational procedures, evaluation, and conditions for achievement, 4) The policy proposals and practical proposals for promoting literacy leadership for school administrators were related agencies, regulatory agencies, promotion, cultivation, and follow-up and expand the results to educational institutions.